The Effect of Career Development and Work Discipline on Employee Performance at PT. XYZ in the ABC Region - Ferdinald Maxcius Pandapotan Sinaga; Ratri Wahyuningtyas (PT. Publikasiku Academic Solution, 2026)
XYZ ABC Region is a company engaged in courier and financial services that has a big responsibility in maintaining service quality and distribution timeliness. However, employee performance in this company does not meet the target, which is suspected to be caused by internal factors such as career development and work discipline. The purpose of this study is to determine the effect of career development and work discipline on employee performance with a case study conducted at PT. XYZ ABC Region. This study uses a quantitative approach with a descriptive method. The research sample consisted of 109 employees of PT. XYZ Region ABC, with data analysis techniques using Structural Equation Modeling–Partial Least Square (SEM-PLS). The independent variables in this study were career development and work discipline, while the dependent variable was employee performance. The results of the study show that career development has a positive and significant effect on employee performance, which means that the better the career development program implemented by the company, the higher the employee performance. In addition, work discipline also has a positive and significant effect on employee performance, indicating that compliance with regulations and effective use of time are important factors in increasing productivity. Simultaneously, career development and work discipline contribute significantly to improving employee performance at PT. XYZ Region ABC. These findings are expected to provide input for company management in designing more effective human resource development strategies through improving structured career systems and consistent enforcement of work discipline to support the achievement of organizational goals in a sustainable manner.